TEACHERS’ PEDAGOGICAL STRATEGIES FOR INTEGRATING LOCAL WISDOM INTO LANGUAGE EDUCATION IN INDONESIAN MULTILINGUAL CLASSROOMS - Dyoty Auliya Vilda Ghasya; Helminsyah Helminsyah; Nurul Fatehah Binti Norhazaruddin (Sensei International Journal of Education and Linguistic, 2023)
Local wisdom has become an important pedagogical resource in language education because it connects language learning with students’ cultural identity, community knowledge, and everyday communicative practices. However, language classrooms are often dominated by textbook-based instruction and standardized linguistic targets that provide limited space for students’ local cultural experiences. This study aims to examine teachers’ pedagogical strategies for integrating local wisdom into language education and to analyze how these strategies support students’ classroom engagement and intercultural awareness. The study employed a mixed-method design involving 48 language teachers, 192 students, 12 teacher interviews, 8 classroom observations, and 24 teaching documents. Quantitative data were analyzed using descriptive statistics and correlation analysis, while qualitative data were examined through thematic analysis. The findings indicate that teachers integrated local wisdom through contextualized materials, local narratives, cultural resource mapping, translanguaging practices, community-based tasks, and reflective intercultural assessment. Contextualized teaching materials were the most frequently used strategy (M = 4.32; SD = 0.51), followed by local narratives and oral traditions (M = 4.15; SD = 0.57). Reflective intercultural assessment was least frequently implemented (M = 3.08; SD = 0.79), although it showed the strongest correlation with intercultural awareness (r = 0.62; p < .01). The study concludes that local wisdom should be positioned as a pedagogical foundation for culturally responsive, multilingual, and reflective language education.